Individual optical variability of active galactic nuclei from the MEXSAS2 sample. Issue 4 (6th November 2020) - Laurenti, M; Vagnetti, F; Middei, R; Paolillo, M
ABSTRACT: At present, most of the variability studies of active galactic nuclei (AGNs) are based on ensemble analyses. Nevertheless, it is interesting to provide estimates of the individual variability properties of each AGN, in order to relate them with intrinsic physical quantities. A useful data set is provided by the Catalina Surveys Data Release 2 (CSDR2), which encompasses almost a decade of photometric measurements of ∼500 million objects repeatedly observed hundreds of times. We aim to investigate the individual optical variability properties of 795 AGNs originally included in the Multi-Epoch XMM Serendipitous AGN Sample 2 (MEXSAS2). Our goals consist of (i) searching for correlations between variability and AGN physical quantities and (ii) extending our knowledge of the variability features of MEXSAS2 from the X-ray to the optical. We use the structure function (SF) to analyse AGN flux variations. We model the SF as a power law, SF(τ)=A (τ /τ _0)^γ, and we compute its variability parameters. We introduce the V-correction as a simple tool to correctly quantify the amount of variability in the rest frame of each source. We find a significant decrease of variability amplitude with increasing bolometric, optical and X-ray luminosity. We obtain the indication of an intrinsically weak positive correlation between variability amplitude and redshift, z . Variability amplitude also appears to be positively correlated with αox . The slope of the power-law SF, γ, is weakly correlated with the bolometric luminosity L bol and/or with the black hole mass M BH . When comparing optical to X-ray variability properties, we find that X-ray variability amplitude is approximately the same for those AGNs with larger or smaller variability amplitude in the optical. On the contrary, AGNs with steeper SF in the optical do present steeper SF in the X-ray, and vice versa.